DIFFERENCES AND SIMILARITIES BETWEEN ENGLISH AND UZBEK CASES (Journal of Science-Innovative Research in Uzbekistan, 2024)
In this scientific article the similarities of the cases in English and Uzbek also point out the differences between them.The article provides a number of examples of the importance of agreements in Uzbek and English. it is highly proved that by this article some problems, complexities of grammar will be to some extent solved. From this article not only ESL student manage to use but also native speekers of English can utilize in acquiring Uzbek in the Future